2022
DOI: 10.1108/ilt-08-2021-0288
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of elliptical dam bearing lubricated with micropolar fluid

Abstract: Purpose This paper aims to evaluate the theoretical performance of elliptical dam bearing (EDB). The objective of this paper is to study the influence of eccentricity ratio, dam parameters and micropolarity parameters on the stability of EDB with respect to micropolar lubrication. Design/methodology/approach In this study, the modified Reynolds’ equation for dynamic state is solved using the finite element method and Galerkin technique. A MATLAB code is written to compute pressure and stability and also to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…In the dynamic analysis of micropolar lubricated offset bearing, Sharma and Krishna 37 concluded that higher offset provides better stability in terms of threshold speed. Very recently, the stability of micropolar lubricated elliptical dam bearing was presented by Sharma et al 38 Above studies [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] reflect that micropolar lubrication provides improved static and dynamic performance of circular and non-circular journal bearing configurations, as compared with Newtonian lubrication.…”
Section: Introductionmentioning
confidence: 99%
“…In the dynamic analysis of micropolar lubricated offset bearing, Sharma and Krishna 37 concluded that higher offset provides better stability in terms of threshold speed. Very recently, the stability of micropolar lubricated elliptical dam bearing was presented by Sharma et al 38 Above studies [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] reflect that micropolar lubrication provides improved static and dynamic performance of circular and non-circular journal bearing configurations, as compared with Newtonian lubrication.…”
Section: Introductionmentioning
confidence: 99%
“…They observed that the higher offset provides better stability in terms of increased threshold speed and decreased whirling. The stability of the elliptical bearing, considering the dam in the upper half, was computed by Sharma et al (2022). They presented the effect of dam and fluid parameters on stability parameters such as critical mass, threshold speed and whirling ratio.…”
Section: Introductionmentioning
confidence: 99%